Aberrant Default Mode Network Underlying the Cognitive Deficits in the Patients With Late-Onset Depression - Liu, Xiaoyun; Jiang, Wenhao; Yuan, Yonggui (Frontiers in Aging Neuroscience, 2018)
Late onset depression (LOD) is regarded as a risk factor or a prodrome of Alzheimer’s disease (AD). Moreover, LOD patients with cognitive deficits have higher risk of subsequent AD. Thus, it is necessary to understand the neural underpinnings of cognitive deficits and its pathological implications in LOD. Consistent findings show that the default mode network (DMN) is an important and potentially useful brain network for the cognitive deficits in LOD patients. In recent years, genetics has been actively researched as a possible risk factor in the pathogenesis of LOD. So, in this review, we discuss the current research progress on the cognitive deficits and DMN in LOD through a combined view of brain network and genetics. We find that different structural and functional impairments of the DMN might be involve in the etiological mechanisms of different cognitive impairments in LOD patients.